$$\newcommand{\id}{\mathrm{id}}$$ $$\newcommand{\Span}{\mathrm{span}}$$ $$\newcommand{\kernel}{\mathrm{null}\,}$$ $$\newcommand{\range}{\mathrm{range}\,}$$ $$\newcommand{\RealPart}{\mathrm{Re}}$$ $$\newcommand{\ImaginaryPart}{\mathrm{Im}}$$ $$\newcommand{\Argument}{\mathrm{Arg}}$$ $$\newcommand{\norm}[1]{\| #1 \|}$$ $$\newcommand{\inner}[2]{\langle #1, #2 \rangle}$$ $$\newcommand{\Span}{\mathrm{span}}$$

$$\newcommand{\vecs}[1]{\overset { \scriptstyle \rightharpoonup} {\mathbf{#1}} }$$ $$\newcommand{\vecd}[1]{\overset{-\!-\!\rightharpoonup}{\vphantom{a}\smash {#1}}}$$$$\newcommand{\id}{\mathrm{id}}$$ $$\newcommand{\Span}{\mathrm{span}}$$ $$\newcommand{\kernel}{\mathrm{null}\,}$$ $$\newcommand{\range}{\mathrm{range}\,}$$ $$\newcommand{\RealPart}{\mathrm{Re}}$$ $$\newcommand{\ImaginaryPart}{\mathrm{Im}}$$ $$\newcommand{\Argument}{\mathrm{Arg}}$$ $$\newcommand{\norm}[1]{\| #1 \|}$$ $$\newcommand{\inner}[2]{\langle #1, #2 \rangle}$$ $$\newcommand{\Span}{\mathrm{span}}$$ $$\newcommand{\id}{\mathrm{id}}$$ $$\newcommand{\Span}{\mathrm{span}}$$ $$\newcommand{\kernel}{\mathrm{null}\,}$$ $$\newcommand{\range}{\mathrm{range}\,}$$ $$\newcommand{\RealPart}{\mathrm{Re}}$$ $$\newcommand{\ImaginaryPart}{\mathrm{Im}}$$ $$\newcommand{\Argument}{\mathrm{Arg}}$$ $$\newcommand{\norm}[1]{\| #1 \|}$$ $$\newcommand{\inner}[2]{\langle #1, #2 \rangle}$$ $$\newcommand{\Span}{\mathrm{span}}$$

1. If $$e=1$$, then $$Y^{2}=\rho (\rho -2X)$$; if $$e\neq 1\left(X+\frac{e\rho}{1-e^{2}} \right)^{2}+\frac{Y^{2}}{1-e^{2}}=\frac{\rho ^{2}}{(1-e^{2})^{2}}$$ if; $$e<1$$ let $$X_{0}=-\frac{e\rho }{1-e^{2}},\: a=\frac{\rho }{1-e^{2}},\: b=\frac{\rho}{1-e^{2}}$$

2. Let $$h=r_{0}^{2}\theta _{0}'$$; then $$\rho = \frac{h^{2}}{k},\:e=\left[\left(\frac{\rho }{r_{0}}-1 \right)^{2}+\left(\frac{\rho r_{0}'}{h} \right)^{2} \right]^{1/2}$$. If $$e=0$$, then $$\theta _{0}$$ is undefined, but also irrelevant if $$e\neq 0$$ then $$\phi = \theta _{0}-\alpha$$, where $$-\pi\leq\alpha <\pi\cos\alpha =\frac{1}{e}\left(\frac{\rho }{r_{0}}-1 \right)$$ and $$\sin\alpha =\frac{pr_{0}'}{eh}$$.

3.

1. $$e=\frac{\gamma _{2}-\gamma _{1}}{\gamma _{1}+\gamma _{2}}$$
2. $$r_{0}=R\gamma _{1},\: r_{0}'=0$$, $$\theta _{0}$$ arbitrary, $$\theta _{0}'=\left[\frac{2g\gamma _{2}}{R\gamma _{1}^{3}(\gamma _{1}+\gamma _{2})} \right]^{1/2}$$

4. $$f(r)=-mh^{2}\left(\frac{6c}{r^{4}}+\frac{1}{r^{3}} \right)$$

5. $$f(r)=-\frac{mh^{2}(\gamma ^{2}+1)}{r^{3}}$$

6.

1. $$\frac{d^{2}u}{d\theta ^{2}}+\left(1-\frac{k}{h^{2}} \right)\: u=0,\: u(\theta _{0} )=\frac{1}{r_{0}},\:\frac{du(\theta _{0})}{d\theta }=-\frac{r_{0}'}{h}$$
2. with $$\gamma = \left| 1-\frac{k}{h^{2}} \right| ^{1/2}$$
1. $$r=r_{0}\left(\cosh\gamma (\theta - \theta_{0})-\frac{r_{0}r_{0}'}{\gamma h}\sinh\gamma (\theta -\theta_{0}) \right)^{-1}$$
2. $$r=r_{0}\left(1-\frac{r_{0}r_{0}'}{h}(\theta -\theta _{0}) \right)^{-1}$$
3. $$r=r_{0}\left(\cos\gamma (\theta -\theta_{0})-\frac{r_{0}r_{0}'}{\gamma h}\sin\gamma (\theta-\theta_{0}) \right)^{-1}$$